Minimally invasive non-fusion vertebral body stabilization in severe benign and malignant fractures. Stent-screw Assisted Internal Fixation: the SAIF technique. Issue 1 (11th June 2019) - Cianfoni, Alessandro; Distefano, Daniela; Hirsch, Joshua; Bonaldi, Giuseppe; Reinert, Michael; Isalberti, Maurizio
This short review focuses on clinical and therapeutic issues posed by severe osteoporotic and neoplastic insufficiency vertebral fractures and on the potential use of a new technique to obtain minimally invasive vertebral body reconstruction, augmentation, and stabilization in such severe fractures, combining two preexisting procedures. The implant of vertebral body stents is followed by insertion of percutaneous, fenestrated, cement-augmented pedicular screws that act as anchors to the posterior elements for the cement–stent complex. This procedure results in a 360° nonfusion form of vertebral internal fixation that may empower vertebral augmentation and potentially avoid corpectomy in challenging osteoporotic and neoplastic fractures.